Implementasi Social-Bricolage Entrepreneurship dan Digital Marketing sebagai Strategi Resiliensi Pelaku Program Pekarangan Pangan Lestari - Umu Khouroh; Christina Sri Ratnaningsih; Bayu Rahayudi; Irany Windhyastiti (Jurnal Bisnis dan Manajemen, 2022)
This study aims to examine the effect of P2L program (social-bricolage entrepreneurship) on P2L business performance and to examine the role of digital marketing as mediating effect of social-bricolage entrepreneurship on P2L business performance. This research is explanatory research with a quantitative approach. The sample in this study is the manager/member of the P2L program group in Malang Regency and collected as many as 62 respondents from 30 P2L groups. Data analysis used the SEM-PL. The research findings show that social-bricolage entrepreneurship does not have a significant effect on the business performance of P2L group managers/members, but has a major impact on the use of digital marketing strategies so as to improve performance. This finding means that digital marketing has a full mediation role in the relationship between social-bricolage entrepreneurship and P2L business performance. In addition to explaining this relationship, this research also shows the need to frame the role of digital marketing within this framework, so that it can provide maximum benefits. Given this important role, managers/members of the P2L group should make maximum use of the existing digital platforms, both freely available and with support from relevant stakeholders.